The Story of writing (Filmstrip) - Webster Publishing Company. [from old catalog] (Webster Pub. Co.: Made by David J. Goodman, inc., 1959)
Captioned drawings trace the history of written communication from the cave drawings of primitive man to the present-day dictionary. Points out how some of the commonly used conventions of writing developed.
Eastman color.
With teacher's guide.
CREDITS: Developed by Paul T. Luebke.
Keywords: Writing -- History